Vestiges of Military Rule in Democratic Governance in Nigeria - Oladipo, Temidayo David (Àgídìgbo: ABUAD Journal of the Humanities, 2017)
The position argued for in this paper is that: the inability to manage Nigeria as a federation; challengesin the area of fiscal federalism, the culture of political apathy, the culture of lack of accountability, contempt for the rule of law, gross disregard for and abuse of fundamental human rights, intolerance for opposition and other vices that eventually undermined the capability of democratic institutions, after democratisation in Nigeria, are vestiges of military rule in Nigeria. When Nigeria returned to democracy in 1999, it was after many years of military rule. However, since the values that military governance stands for are different from those of democracy, there is the need to evaluate how many years under military despotism have rubbed off on the institutions of democracy as we have it in Nigeria today. It is pointed out in the paper that the military years that preceded the establishment of democracy in Nigeria promoted conditions, mentalities, and practices among Nigerians that are constituting hindrancesto the optimal performance of democracy in the country. This happened because democracy met in place conditions that are incompatible with norms, values, purposes, and structures that are suitable for the sustenance of democratic culture such that the rule of law, consensus-building, tolerance, free and fair election, accountability, checks and balances and other values of democracy are struggling for survival. It was concluded that the right democratisation process for Nigeria should include developing a mentality in Nigerians that is conducive for democracy to thrive. This requires the cultivation of the values of democracy in the minds of Nigerians and disabusing their minds from the anomalies associated with military rule.